Improved synthesis of amino acid and dipeptide chloromethyl esters using bromochloromethane - Gomes, P (2015)
Peptide chloromethyl esters are important compounds in prodrug synthesis. A simple, mild and efficient method for the synthesis of chloromethyl esters of N-blocked amino acids and dipeptides using exclusively bromochloromethane is reported. These N-blocked amino acid and dipeptide chloromethyl esters react readily with the carboxylic acid group of aspirin and with the sulfonamido group of the antimalarial sulfamethazine, to give the corresponding prodrugs.